(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper discusses about the move of demonetization taken by central government of India on 8th November 2016, with respect to its reasons and effects on different sectors on India. The sectors cover micro-Business, E-wallet businesses, online retail stores and so on. This paper is based on the experience of impact of demonetization in different sectors and to analyze the current and immediate impact of demonetization on Indian economy. The paper is based on secondary data collection methods. Government of India has demonetized the currency of Rs.500 and Rs.1000 on 8th November 2016, aimed to address corruption, counterfeit currency, black money and terror financing. The total value of demonetized currency was Rs. 15.4 trillion, which constituted around 86.9 of total currency in circulation. The study conducted in this paper reveals that demonetization influenced various economic sectors differently. The highly impacted period due to demonetization was experienced especially during November and December 2016. This impact was moderated prominently in the month of January 2017 and immoderate to a longer extent by mid of February 2017. As an impact of demonetization on Indian banks, there is a positive change in the financial statements of scheduled commercial banks. The huge amount of deposited in the banks has raised and created surplus liquidity conditions. A significant increase in total number of accounts opened under the scheme of Pradhan Mantri Jan Dhan Yogna and the amount deposits in these accounts have also increased. A weighty impact of demonetization has also been monitored in the use of electronic banking transactions. This study is descriptive in nature and the data has been taken for the period of pre-demonetization and post- demonetization.